A portrait of China's economic transformation: from manufacturing to services. Issue 1 (2nd January 2023) - Zhang, Bin; Zhu, He; Zhang, Jiajia
ABSTRACT: The Chinese economy marked a turning point around 2010 to 2012, with economic growth, expenditure structure, industrial structure, and other macroeconomic indicators running counter to their earlier trends. There was a common cause behind all the changes: economic transformation from manufacturing to services. Starting with saturation in demand for manufactured goods, household consumption began to shift toward more human capital – intensive services, which led to a chain of effects in the industrial structure, slower economic growth, altered labor flows, as well as changes in the features of the business cycle. Compared with other high-income economies when they were at a similar development stage, China's economic transformation from manufacturing to services has been the standard practice.